Anthropogenic land‐use change intensifies the effect of low flows on stream fishes. Issue 1 (20th October 2019) - Walker, Richard H.; Girard, Carlin E.; Alford, Samantha L.; Walters, Annika W.
Abstract: As ecosystems experience simultaneous disturbances, it is critical to understand how multiple stressors interact to affect ecological change. Land‐use change and extreme flow events are two important stressors that could interact to affect fish populations. We evaluated the individual and interactive effects of discharge and land‐use change associated with oil and natural gas development on populations of two stream fishes over a 7‐year period. We used repeated‐state (i.e. abundance trends) and rate (i.e. colonization and persistence) responses to advance our understanding of flow‐ecology relationships in a multiple‐stressor framework. Overall, fish abundance, colonization and persistence declined as discharge decreased. The effect of land‐use change associated with oil and natural gas development differed between species, with the abundance of Mottled Sculpin declining and Mountain Sucker increasing as land‐use change increased. We found both synergistic and antagonistic interactions between discharge and land‐use change. Land‐use change intensified the effect of low flows for Mottled Sculpin and lead to greater variability in responses to flow for Mountain Sucker. These differences between species' responses are likely due to differences in their physiological tolerances and behavioural adaptations to disturbance. Synthesis and applications . Our research provides empirical evidence for the complex interactions that can arise between discharge and anthropogenic land‐use change. Management efforts to reduce inputs of sediments and chemical contaminants associated with land‐use change (e.g. silt fences, vegetative buffers) and promote quality refuge habitats (i.e. in‐stream habitat restoration) could help mitigate the negative effects of low‐flow extremes on stream fishes. Further development of flow‐ecology relationships in a multiple‐stressor framework will help guide management of stream fishes, and provide a better understanding of the mechanisms underlying responses of different species. Abstract : Our research provides empirical evidence for the complex interactions that can arise between discharge and anthropogenic land‐use change. Management efforts to reduce inputs of sediments and chemical contaminants associated with land‐use change (e.g. silt fences, vegetative buffers) and promote quality refuge habitats (i.e. in‐stream habitat restoration) could help mitigate the negative effects of low‐flow extremes on stream fishes. Further development of flow‐ecology relationships in a multiple‐stressor framework will help guide management of stream fishes, and provide a better understanding of the mechanisms underlying responses of different species.